Evaluation the Impact of Spatial Configuration on Socio-Economic Parameters in Emerging Shopping Centers. Case study of Ritaj Mall in Constantine, Algeria (International Journal of Built Environment and Sustainability, 2022)
This article questions the impact of the spatial configuration on user behavior and economic performance in the multi-level shopping center of Ritaj Mall in Constantine, Algeria. For ten years, large private real estate operators invest in different kinds of commercial building. The arrival of this new shopping complex in Algerian cities sis an opportunity to examine the question of architectural quality, especially that numerous papers and the theses have criticized the architectural production in Algerian, mainly in the residential and public sectors. Through the spatial analysis of the circulation spaces, the movement distribution and the architectural design parameters, the objective of this text is to better understand the correlation between “conceived” spaces and “lived” spaces. Their correlation constitutes a determining index of spatial qualities. For this purpose, an analysis is adopted according to a method of space syntax and completed by empirical surveys, and statistical correlation. Essentially, this paper shows that the axiality and interconnectedness of spaces largely determine the spatial quality of a commercial building. In addition, the central space (atrium) plays a determining role in the distribution of user flows over all vertical and horizontal spaces and extensions. It also shows the importance of spatial accessibility parameters in the distribution of economic and social activities
Keywords: Spatial configuration, Atrium, User behavior, Shopping center, Space syntax